Biodegradation potential of polycyclic aromatic hydrocarbons in Taihu Lake sediments. Issue 28 (19th December 2022) - Yan, Zaisheng; Wang, Luming; Yan, Haifeng; Dong, Yibo; Zhang, Guoqing; Wu, Huifang
ABSTRACT : To assess the biodegradation potential of polycyclic aromatic hydrocarbons (PAHs) in sediments, sediment microcosms were constructed with sediments collected from six lake zones with different trophic statuses in Taihu Lake. The presence and concentration of PAH-degrading bacteria (PDB) were estimated by the most probable number (MPN) method. After 85 d of aerobic and anaerobic incubation, spiked PAHs (phenanthrene, pyrene, and benzo[ a ]pyrene) were partially degraded by indigenous sediment microorganisms. Large differences in PAH degradation were observed depending on the molecular size of the PAHs. The PAH removal efficiency in sediments under aerobic conditions was higher than that under anaerobic conditions. MPN analyses showed a higher abundance of degrading microflora in the high PAH-contaminated sites than in the low PAH-contaminated sites. Moreover, the anaerobic PDB populations in the sediments from the six different sites were much higher than those of aerobic PDB. The PAH biodegradation capability in sediments was associated with the geochemical conditions and bacterial populations. PDB showed a broad spatial distribution, thereby implying that they played an important role in the natural attenuation and cycling of PAHs in Taihu Lake. This work indicates that PAHs remain a concern in Taihu Lake sediments and can provide useful information for further bioremediation of PAH-contaminated sediments. GRAPHICAL ABSTRACT: UF0001